Surface engineering of IN-718 by low-temperature carburisation: properties and thermal stability. (4th March 2019) - Li, Z.; Paramasivam, T.; Niu, W.; Wang, Y.; Anderoglu, O.; Heuer, A. H.; Maloy, S. A.; Lillard, R. S.; Ernst, F.
ABSTRACT: IN-718 was surface-engineered by low-temperature gas-phase carburisation, generating a highly concentrated solid solution of interstitial carbon with an average depth of 10   μm and a carbon fraction up to 0.18, exceeding equilibrium solubility by orders of magnitude. Here, we investigate the stability of this highly supersaturated material against heat exposure and proton irradiation. We found: (i) Short-term exposure to high temperature causes de-carburisation. Long-term exposure to moderate (reactor operating) temperature does not. (ii) Exposure to MeV proton irradiation at elevated temperature – as well as high-temperature only – causes partial de-carburisation and precipitation of nanometre-sized Cr-rich carbides. This reduces Cr loss by evaporation. Physical models are proposed to explain the observed phenomena in terms of microscopic mechanisms. In conclusion, low-temperature gas-phase carburisation can significantly improve the properties of IN-718 for technical applications, including nuclear reactors.